Teachers’ Professionalism In Teaching Reading: Narrative Inquiry From A Voice Of Senior EFL Teacher At A Junior High School - Muhammad Yusuf; Acep Bahrum Kamil; Sumarta Sumarta (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2023)
The aims of this research is to open the insight of a senior EFL teacher toward the strategies that commonly use during reading teaching. Using narrative inquiry design, the result of this study would be in narrative form. The participant that chosen in this study is an EFL teacher with 25 years experiences. After collecting the data by interview, the researcher found the result that shows the mostly use strategies are Lecture and Direct Reading Activity. These two strategies come with it advantages and disadvantages. But, these two strategies consider the most effective and efficient to apply in the classroom.